Effect of cinmethylin (LUXIMO®) in combination with non-chemical measures against Alopecurus myosuroides Huds. in winter cereals - Gerhards, Roland; Messelhäuser, Miriam; Sievernich, Bernd; Schönhammer, Alfons (Julius-Kühn-Archiv, 2022)
Pre-emergence herbicides in winter annual cereals often need to be combined with other weed control tactics to provide sufficient weed control efficacy for the entire growing season. In the present study, the new pre-emergence herbicide cinmethylin for the control of Alopecurus myosuroides Huds. in Europe was tested in four field experiments in winter wheat and winter triticale in Southwestern Germany over a period of three years. Treatments with cinmethylin were combined with stubble treatments and delayed drilling of winter annual cereals in a three-factorial block design. Average densities of A. myosuroides in the untreated control plots ranged from 38-1233 plants m-2. The pre-emergence herbicide Cinmethylin controlled 58-99% of A. myosuroides plants until 120 days after sowing. Additive and synergistic effects of cinmethylin and delayed drilling were found for all studies reducing A. myosuroides density by more than 90%. Stubble treatments including one and two passes of chisel ploughing, chisel ploughing followed by glyphosate application and conversation stubble tillage with a straw harrow did not result in significant different A. myosuroides densities in the following winter cereal crops. Winter wheat and winter triticale grain yields were significantly increased by cinmethylin and delayed drilling. These data underline the benefits of integrated weed management using different weed control tactics.